Trends for Surgical Treatment of Testicular Varicocele: A German Whole-population Analysis of Inpatient Procedures from 2006 to 2021 - Cem Aksoy; Philipp Reimold; Philipp Karschuck; Subhajit Mandal; Nicole Eisenmenger; Christer Groeben; Aristeidis Zacharis; Johannes Huber; Luka Flegar (European Urology Open Science)
Background and objective: Testicular varicocele (TVC) is a common benign finding in men of all ages. Indications for TVC repair are abnormal sperm parameters and testicular pain. The optimal surgical method for TVC repair is still a matter of controversy. The aim of our study was to analyze the current situation and trends for TVC surgery in Germany. Methods: The German reports for hospital quality were analyzed from 2006 to 2021. Linear regression models were applied to detect trends over time. Outpatient procedure rates were estimated. Key findings and limitations: A total of 38 653 inpatient TVC surgeries were included. Total varicocelectomy procedures decreased from 3456 in 2006 to 2165 in 2021 (−37.4%; p < 0.001). The proportion of open TVC procedures remained constant at ∼25%. The proportion of laparoscopic TVC procedures increased from 25% in 2006 to 45% in 2021 (p < 0.001), while the sclerotherapy rate for TVC treatment decreased from 47% in 2006 to 29% in 2021 (p < 0.001). In 2006, 543 hospitals offered TVC treatment, which decreased to 466 hospitals in 2021 (−14.2%). Among patients undergoing surgical TVC procedures in 2021, 75% were younger than 35 yr. We estimated an increase in outpatient procedures from 365 cases in 2013 to 1330 cases in 2021 (p < 0.001). The estimation for outpatient procedures represents a study limitation. Conclusions and clinical implications: Laparoscopic TVC treatment is the dominant surgical approach. However, one in three patients receives sclerotherapy for TVC in Germany. While fewer hospitals offer the treatment, we observed a trend for centralization, with an increase in high-caseload departments, as well as an increasing trend for outpatient treatment. Patient summary: TVC is a collection of swollen veins in the testicle. We analyzed treatment trends in Germany for this condition from 2006 to 2021. There was an increase in the use of keyhole surgery over time, and we estimate that the percentage of day-case surgeries also increased.